The survival of the U.S. dual class share structure - Howell, Jason W. (Journal of Corporate Finance, 2017)
In his groundbreaking work “Uncertainty, Evolution, and Economic Theory,” Armen Alchian (1950) suggests that survival is the real test of a firm's success. In this paper, I apply the survival test to the use of dual class share structures in the United States. Beginning with its original implementation by the International Silver Company in 1898 to the prevalence of dual class initial public offerings in 2013, I review the evolution and continued sustainability of the dual class structure in the United States. I contrast the structure with the failed use of tracking stocks and illustrate the structure's continued resilience alongside “competitive” anti-takeover devices such as poison pills, staggered boards, and supermajority voting requirements. Despite the external challenges from legislative bodies, shareholder rights groups, and institutional investors, the dual class structure has survived as an alternative means to raise capital for founders and/or controlling stockholders.